Development of an allele-specific polymerase chain reaction genotyping test and association of selected single nucleotide polymorphisms and analytes with the risk of alzheimer’s disease / Mohd Nazif Samat @ Darawi - Samat @ Darawi, Mohd Nazif (Institute of Graduate Studies, UiTM, 2014)
The incidence of Alzheimer”s disease (AD) is expected to increase exponentially as the population ages. Continuing research in this area is essential to better understand this disease and develop strategies for prevention and treatment. Recent genome-wide association studies have identified several novel loci as genetic risk factors of AD. Previous studies also suggest the total plasma homocysteine (tHcy) level and its biological determinants such as folate and vitamin B12 contribute to the risk of AD. Some of them highlight the correlation between AD risk and genetic polymorphisms of methylenetetrahydrofolate reductase (MTHFR) and transcobalamin (TCN II) since they are directly associated with the Hcy metabolism.